ผลของรังสีแกมมาต่อเปอร์เซ็นต์การงอกของเมล็ด การเจริญเติบโต และการรอดชีวิตในข้าวพันธุ์ กข47 - ศิริงาม ธนภูมิ; พงษ์ประยูร วาสินี (Thai Journal of Science and Technology, 2020)
Rice (Oryza sativa L. cv. RD47) is a high yield rice cultivar with good quality of rice milling, but it is sensitive to the bacterial leaf blight disease. In the present, the radiation was utilized in the genetic variation to induce plant diversity. Therefore, this research aims to establish the effect of various gamma ray concentrations at 0, 100, 200, 300, 400 and 500 Gy, on the seed germination, growth and survival percentage of RD47 rice cultivar. The rice seeds were exposed 7.37 Gy/min gamma ray at nuclear technology research center, Kasetsart University. This research was designed as a completely randomized design (CRD) with 6 treatments, and 4 replications per treatment. The results showed that the gamma ray concentration affected seed germination, growth and survival percentage of RD47 rice cultivar. The highest of the seed germination and survival percentages were found in the non-radiated gamma ray (0 Gy) of RD 47 rice cultivar at 96.50±1.55% and 100.00±0.00%, respectively. In addition, plant height and root number were reduced when subjected to gamma ray concentration after seed germination for 14 days. The lethal death at 30 days after seeding (LD50(30)) of the gamma ray concentration was 278.01 Gy.